2022
DOI: 10.3389/fpsyt.2022.1013569
|View full text |Cite
|
Sign up to set email alerts
|

Role of maintenance treatment on long-term efficacy of bilateral iTBS of the prefrontal cortex in treatment-seeking cocaine addicts: A retrospective analysis

Abstract: CUD, like other addictions, is a chronic disease characterized by a high rate of relapse and drop-out (DO) from medical and behavioral treatment programs, which is positively correlated with relapse. Repetitive transcranial Magnetic Stimulation (rTMS) protocols have shown therapeutic potential in addiction in the short term, but only a few studies have explored their long-term efficacy, so far. This study explores the long-term outcome of bilateral intermittent theta-burst stimulation (iTBS) of the prefrontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The initial follow-up study [90], demonstrated that rTMS treatment had a lasting effect in reducing cocaine consumption. Similarly, Sanna et al [115], found comparable results and highlighted the importance of a maintenance protocol to maintain abstinence and decrease the rate of patient withdrawal over time. Furthermore, a single-participant study using active DBS targeting the nucleus accumbens showed a significant reduction in cocaine cravings and consumption [116].…”
Section: Cocainementioning
confidence: 81%
“…The initial follow-up study [90], demonstrated that rTMS treatment had a lasting effect in reducing cocaine consumption. Similarly, Sanna et al [115], found comparable results and highlighted the importance of a maintenance protocol to maintain abstinence and decrease the rate of patient withdrawal over time. Furthermore, a single-participant study using active DBS targeting the nucleus accumbens showed a significant reduction in cocaine cravings and consumption [116].…”
Section: Cocainementioning
confidence: 81%
“…Finally, there appears to be a brief period of increased plasticity post-stimulation that can be exploited to reinforce learning by way of personalized motivational statements. One of the most recent studies in the cocaine use field highlighted the importance of a maintenance protocol for the sake of evaluating long-term outcomes in this population [76]. The durability of effects is most important for successful addiction treatment, and future studies should ideally conduct follow-up measurements after the completion of the acute TMS intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Both treatments had low dropout rates and similar safety and tolerability profiles. The same group explored the long-term outcome of iTBS with the H4 coil in CUD and the possible influence of maintenance treatments on abstinence and drop-out rates [76]. In a retrospective analysis of 89 patients who were exposed to 20 sessions of iTBS, 61 (81%) patients were abstinent at the end of treatment and were followed up for 12 months.…”
Section: Cocaine Use Disordermentioning
confidence: 99%